Patogenitas Edwarsiella tarda Pada Ikan Sidat (Anguilla marmorata) Selama Penyimpanan Beku -25°C - Arsal Arsal; Asriani Hasanuddin; Ahmad Rizal (Mitra Sains, 2016)
The purpose of this study is to determine the patogenechity (ability to cause death) of the Edwarsiella tarda in fish eel (Anguilla marmorata) which have frozen and stored at a temperature of -25°C for 15, 25 and 35 days. Patogenecity was tested with methode by isolating E. tarda from the meat of frosen Eel that what stored for 15, 25 and 35 days ago carried infected to eels the size of 120-122 grams with injecting isolate bacteria Edwarsiella tarda is intraperitoneally as much as 0,1 ml/ind at a dose of 108 CFU/ml (standard 1 Mac Farland), then maintened and observed for 15 days. Pathogenicity test results based on mortality / death of the fish indicates that the bacteria Edwarsiella tarda taken from frozen eel fish stored for 15, 25 and 35 days at temperatures-25oC were still survive and still are pathogenic to fish eel with a tendency the longer the storage time, it will decrease the mortality rate / patogenitasnya. Results of analysis of variance showed mortality observed eel (Anguilla marmorata) with a storage time of 15 days and 25 days resulted in a significantly different effect than the storage time of 35 days with a storage temperature -25oC.